2014
DOI: 10.1021/jf5019593
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Rich Water Reestablishes ROS Homeostasis but Exerts Differential Effects on Anthocyanin Synthesis in Two Varieties of Radish Sprouts under UV-A Irradiation

Abstract: The aims of the study were to investigate whether hydrogen gas (H2) was involved in regulation of anthocyanin biosynthesis in two contrasting radish (Raphanus sativus L.) varieties (low [LA] and high [HA] level of anthocyanin) under UV irradiation. The results showed that hydrogen-rich water (HRW) significantly blocked the UV-A-induced increase of H2O2 and O2(•-) accumulation, and enhanced the UV-A-induced increase of superoxide dismutase (SOD) and ascorbate peroxidase (APX) activities in LA and HA. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 49 publications
2
60
0
Order By: Relevance
“…Similar antioxidant behaviours of exogenous H 2 have been reported in studies of plant tolerance of abiotic stresses (e.g. Xie et al, 2012Xie et al, , 2014Xie et al, , 2015Cui et al, 2013Cui et al, , 2014Jin et al, 2013;Xu et al, 2013;Su et al, 2014).…”
Section: Hydrogen Alleviated Boron Toxicity By Modulating Ros Homeostsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar antioxidant behaviours of exogenous H 2 have been reported in studies of plant tolerance of abiotic stresses (e.g. Xie et al, 2012Xie et al, , 2014Xie et al, , 2015Cui et al, 2013Cui et al, , 2014Jin et al, 2013;Xu et al, 2013;Su et al, 2014).…”
Section: Hydrogen Alleviated Boron Toxicity By Modulating Ros Homeostsupporting
confidence: 79%
“…Similar to the approach used in animals, hydrogen-rich water was regarded as a safe and easily available means of investigating the physiological function of endogenous H 2 in plants. It has been shown that H 2 might be a novel bioregulator involved in phytohormone signalling , the delay of fruit senescence (Hu et al, 2014) and plant responses to various stresses, including paraquat (Jin et al, 2013), ultraviolet radiation (Su et al, 2014;Xie et al, 2015), drought (Xie et al, 2014), salinity (Xie et al, 2012;Xu et al, 2013), cadmium and mercury exposure (Cui et al, 2014). However, whether H 2 regulates plant adaptive responses to B toxicity is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, improving the selenium content in food, improving peoples’ daily selenium intake is important. As an industrialized large‐scale vegetable, radish sprouts have gained popularity in East Asian countries, so radish sprouts are an ideal material for selenium‐fortified vegetables (Su et al., ; ). In this study, we treated radish sprouts with Na 2 SeO 3 and Na 2 SeO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The determination of anthocyanin content in the radish hypocotyls was according to the method developed by Su et al (2014), which involves measuring the absorbance (530) of extracts.…”
Section: Methodsmentioning
confidence: 99%
“…Primer Expressversion 3.0 (Applied Biosystems) was used to design all PCR primers targeting actin, PAL, CHS, CHI, F3H, DFR, LDOX, ANS , and UFGT (Su et al, 2014). All primers (Supplementary Table 1) were synthesized by Genewiz Bio-engineering Ltd. Company (Suzhou, China).…”
Section: Methodsmentioning
confidence: 99%